Sequências didáticas potencialmente significativas com enfoque CTS : uma proposta para qualificar o ensino de reações químicas - Amaral, Luana Carla Zanelato do (2016)
This paper consists in development, application and reports of the implementation of a sequence of activities involving the theme Chemical Reactions, as an educational product of a professional master s work of the Programa de Pós-Graduação em Ensino de Ciências e Matemática of the Universidade de Passo Fundo, within the line of research Theoretical and Methodological Basis for the teaching of Science and Mathematics. The educational product is the elaboration of a didactic sequence, based on the Theory of Meaningful Learning by David Ausubel, mainly focusing on the Marco Antonio Moreira ideas and the Potentially Significant Teaching Units (PSTUs). It was also used the approach in Science, Technology and Society (STS) in order to introduce the Chemical content/concepts. The work was developed aiming to meet the prospects of the Ensino Médio Politécnico, modality adopted by the educational system of the state of Rio Grande do Sul since 2012, which aims at the integral formation of the student, both for citizenship and professional work. The content established was Inorganic Chemical Reactions, worked in the form of five micro-PSTUs adapted, addressing the following topics: evidence of chemical reactions, weight laws, combustion reaction, dissolution reaction and reactivity of metals. The application of educational product developed was in a school of Rio Grande do Sul educational system, in a class of first grade of high school polytechnic education, starting at the month of June, 2015. Finally, the data collected, that aimed to answer the initial question, occurred through the following research instruments: the participation of students, teacher class memories, notes of students and the production of comic books. These instruments supported evidence that the teaching sequence with STS approach contributes to the construction of meaningful learning, as it addresses the chemical content with themes close to the reality of students, with the potential to drive them to the development of critical thinking, keeping them more interested and motivated about learning.